MENILAI KESESUAIAN QANUN KOMISI KEBENARAN DAN REKONSILIASI ACEH DENGAN ASAS-ASAS PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN - Zahlul Pasha (State of Islamic Institute Langsa, 2019)
This research aim to analyze of parity between the Qanun of Aceh Truth and Reconcialiation Commission and the Law Number 12 Year 2011 on the Law-making Process.The conclusion of this research is establishment of the Qanun of Aceh Truth and Reconciliation Commission seems has trouble with the Law-making Process Principles, specifically on clarity of formulation, hierarchical types and material substances. Furthermore, this situation was leading motive prompting people who are harmed to initiate judicial review